Delayed copying is uniquely related to dictation in bilingual Cantonese–English-speaking children in Hong Kong. Issue 1 (2nd January 2018) - Lo, Jason Chor Ming; Ye, Yanyan; Tong, Xiuhong; McBride, Catherine; Ho, Connie Suk-han; Waye, Mary Miu Yee
ABSTRACT: This study investigated the relationship between copying skills and dictation among Hong Kong children. One-hundred and thirty-four Chinese–English bilingual children were given a series of cognitive-linguistic and literacy measures, including tasks of rapid digit naming, phonological awareness, orthographic knowledge, morphological construction, vocabulary, pure copying, delayed copying and dictation. Most cognitive-linguistic variables were moderately correlated. The association of Chinese to English dictation was a modest .26. The variable that was most strongly associated with Chinese dictation was Chinese delayed copying; the variable most strongly associated with English dictation was English delayed copying. In path analyses, delayed copying was uniquely correlated with dictation in both Chinese (L1) and English (L2); the model was unchanged with the inclusion of dictation of the other orthography, indicating a minimal effect of linguistic transfer of dictation itself in the present study. These results particularly highlight the potential of the delayed copying task, administered and scored differently in Chinese and in English, which may be useful as an indicator of dictation difficulties independently in Chinese and English.